A Systematic Approach to Creating Methods and Forms of Organizing Training in Solving Chemical Problems - Ajiniyazova Sholpan Saparniyazovna (Scientific Trends, 2025)
This article examines the methods and forms of organizing classes in solving problems in chemistry in general secondary schools.
Keywords: System, algorithm, chemical problem, problem, quantitative calculus books, lesson.